Foreign private capital-led growth: the recent rise and fall of Turkey - Tutan, Mehmet Ufuk (Sage Publications Inc, 2455 Teller Rd, Thousand Oaks, Ca 91320 USA, 2016)
This article maintains that after a decade as a poster-child for neoliberal growth, (1) Turkey has definitely fallen from its former impressive growth performance, (2) the cause is exactly the rupture of its foreign capital-led growth model, just as its fragility critics warned, and (3) given the state of both external and internal economic and political factors, there is very little chance of Turkey returning to its strong growth over the next several years.
Keywords: foreign capital-led growth; Turkey; development